2008
DOI: 10.1245/s10434-008-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Resolution of Jaundice Following Biliary Stenting Predicts More Favourable Early Survival in Resected Pancreatic Ductal Adenocarcinoma

Abstract: These results suggest that the presence of jaundice at the time of resection has an adverse impact on early, but not overall, postoperative survival in pancreatic cancer patients undergoing preoperative biliary drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 26 publications
3
37
2
3
Order By: Relevance
“…A major goal of accurate diagnosis and staging is to avoid major pancreatic resection in patients who will not benefit; about 10-15% of patients who have a pancreatic resection have benign disease on final histology 28 and up to 20% of patients will develop recurrent disease 3-6 months post resection. 60 Functional imaging techniques such as PET/CT may add to staging of pancreatic cancer by diagnosing small-volume metastatic disease and differentiating between benign and malignant lesions and it is vital, therefore, that a well-designed prospective study answers this question. A number of studies have addressed the diagnostic accuracy of PET/CT and changes in management as a result of PET/CT.…”
Section: Positron Emission Tomography/computed Tomography In Pancreatmentioning
confidence: 99%
“…A major goal of accurate diagnosis and staging is to avoid major pancreatic resection in patients who will not benefit; about 10-15% of patients who have a pancreatic resection have benign disease on final histology 28 and up to 20% of patients will develop recurrent disease 3-6 months post resection. 60 Functional imaging techniques such as PET/CT may add to staging of pancreatic cancer by diagnosing small-volume metastatic disease and differentiating between benign and malignant lesions and it is vital, therefore, that a well-designed prospective study answers this question. A number of studies have addressed the diagnostic accuracy of PET/CT and changes in management as a result of PET/CT.…”
Section: Positron Emission Tomography/computed Tomography In Pancreatmentioning
confidence: 99%
“…In recent years, several studies have revealed routine preoperative biliary drainage (PBD) to show no benefit over early surgery without PBD. At the time, the use of routine PBD is controversial, as there are studies showing no benefit of omitting PBD (2)(3)(4)(5)(6)(7). However, some surgical centers, including our own, do not usually possess the resources enabling early surgery entailing a need for PBD.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from animal studies suggests that internal biliary drainage to correct hyperbilirubinaemia leads to improved nutritional status, reduced risk of sepsis, and improved immune function [4,6,9]. In the clinical setting, several studies (mainly retrospective cohort studies) suggest that preoperative biliary drainage has little impact on postpancreatectomy morbidity, mortality, or survival [10][11][12][13][14][15]. In addition, some investigators have indicated that the incidence of infective complications among stented patients may be increased after surgery [16].…”
Section: Discussionmentioning
confidence: 99%